Antifungal activity of Trichoderma atroviride against Fusarium oxysporum.f.sp.lycopersici causing wilt disease of tomato - Yogalakshimi, S; Thiruvudainambi, S; Kalpana, K; Thamizh Vendan, K; Oviya, R (Journal of Horticultural Sciences, 2021)
Fusarium oxysporum f. sp. lycopersici causing tropical wilt of tomato is a destructive phytopathogen. To study bio efficacy of fungal bio agents, fifteen isolates of Trichoderma species were isolated from rhizosphere soil of healthy tomato plants. Among the isolates, TA12 showed higher antagonistic efficacy against the pathogen. Upon analysis of the rDNA of internal transcribed spacers (ITS) and molecular data, the isolate was identified as Trichoderma atroviride. The in vitro antagonistic assessment indicated that the T. atroviride isolate caused significant inhibition of F. oxysporum f. sp. lycopersici. Trichoderma atroviride (TA12) showed antagonistic activity against F. oxysporum with mycelial inhibition of 71.25%. The culture filtrates of Trichoderma atroviride exhibited its antifungal activity against F. oxysporum with a suppression of 77.77%. Moreover, the ethyl acetate extracts of T. atroviride TA12 showed the highest antifungal potency against F. oxysporum f. sp. lycopersici. The main bioactive constituents of T. atroviride were 6-pentyl - 2H-pyran-2-one, quinoline, phenol, 2-(6-hydrazino-3-pyridazinyl) and heptadecane. In conclusion, the isolate TA12 could be exploited to develop an effective biocontrol management practice for combating Fusarium wilt disease of Fusarium oxysporum f.sp. lycopersici in tomato.
Keywords: Tomato; Fusarium oxysporum; Trichoderma; GC-MS; Antifungal activity